Response of carbon-basalt hybrid fiber reinforcement polymer under flexural load. (24th July 2018) - Ma, Fangwu; Yang, Meng; Pu, Yongfeng; Zhi, Yongshuai
Abstract: A study on the flexural performance of 6-ply unidirectional hybrid composite laminates reinforced by carbon and basalt fibers is presented in this paper. The hybrid composites were fabricated following the resin transfer molding (RTM) process in an inter-ply configuration with varying plies of basalt fibers added to the surface of carbon laminate. Three-point bending test was carried out according to ASTM D790-10 at a span to depth ratio of 32. The laminates were examined by optical and scanning electron microscopy(SEM), which enabled a better comprehension of the failure modes. The results showed that various failure modes occurred through almost all of the layers and mainly concluded fiber buckling on the compressive side, shear failure on the middle layer, and fiber pull-out on the tensile side. Flexural properties of hybrid composites were strongly dependent on the basalt fibers added to the laminate. When adding two layers of basalt fibers to the laminates, flexural strength of hybrid composites increase most, and it can be seen that the flexural modulus decreased with increasing percentage of basalt fibers. And the experiments showed a positive hybridization effect by substituting carbon fibers with basalt fibers. Here, hybridization of carbon and basalt fibers can improve the balance of the mechanical properties of carbon fiber reinforced polymer(CFRP), thereby extending its application scope and reducing the cost.